Distribution automation on LV and MV using distributed intelligence - Melo, F; Caˆndido, C; Fortunato, C; Silva, N; Campos, F; Reis, P (22nd International Conference and Exhibition on Electricity Distribution (CIRED 2013), 2013)
Nowadays, the electrical energy distribution network is considered to be a critical infrastructure in industrially developed societies. Its protection regarding safety and security threats is increasing awareness and concern. The fact that this infrastructure is geographically spread across large areas brings difficult technological challenges for fault management (real-time prevention, detection, precise location and isolation of anomalies). The distribution automation and fault location in the distribution network is a key task for any operator. Distribution Automation (DA) and electric network monitoring and sensing can reduce outage and repair times, optimise voltage profiles and improve asset management. Advanced DA processes real-time information from sensors, smart meters, Distributed Generation (DG) and network topology for fault location, automatic reconfiguration of feeders, voltage and reactive power optimisation. This paper addresses this subject and describes the technology and functionalities being implemented on a DA pilot project promoted by EDP Distribuiça˜o (EDP Group), Portugal and under InovGrid initiative together with Efface and Silver Spring Networks (SSN). (4 pages)